Climatic classification of Bangladesh - MOBASSHER , A.; HOSSAIN, AHMAD (MAUSAM, 1995)
Using climatological data for 27 years of 16 stations an attempt has been made to classify the climate of Bangladesh by the method of Ivanov (1941. 1956 & 1958). Selianinov (1966). Gorsinkii and Shever (1976). By Ivanov's method it has been established that there are three climatic zones in Bangladesh (i) zone with simple humid climate- western bordering districts of Bangladesh; (ii) zone with sufficient humid climate -areas of Bangladesh mainly to the west of 90. E and (iii) zone with super humid climate areas or Bangladesh mainly to the east of 90"E. Almost analogous climatic zones have been obtained by Selianinov's method. By Gorsinkii's method. it has been shown that there are three climatic zones in Bangladesh' (i) quasi-maritime climate -southeastern and northeastern hilly areas; (ii} climate of the plain land- the central belt of the country. and (iii) quasi-continental clill1ate -western bordering districts. By Shevers method it has been shown that there is only sharp continental type of climate in Bangladesh.